Peran Pendidikan Agama Islam dalam Mecegah Perilaku PMO Pada Remaja di Era Digital - Jam Jam Mujadi, Khoirul; Putri Sifayani, Laysa; Ifan Nrur Hakim, Muhammad; Satria, Panca (ILJ: Islamic Learning Journal, 2025)
The development of digital technology provides easy access to information for adolescents, but on the other hand, it increases the risk of exposure to Porn, Masturbation, and Orgasm (PMO) behaviors that have a negative impact on moral and spiritual development. This study aims to analyze the role of Islamic Religious Education (PAI) in preventing PMO behaviors in adolescents in the digital era. This study uses a mixed method with a descriptive approach. Quantitative data were obtained through a questionnaire distributed to 30 adolescents aged 15–18 years, while qualitative data were obtained through a literature study. The results showed that the internalization of IRE values played an important role in shaping adolescents' moral awareness and self-control, although exposure to negative content in digital media remained a major challenge. The role of schools, families, and the integrated use of Islamic media and digital literacy have been proven to support efforts to prevent PMO behavior. Thus, Islamic Religious Education does not only function as a subject but also as an effective moral fortress in facing the challenges of the digital era.